Honoring Practical Processing Science at TMS 2020 - Pilchak, Adam (JOM (1989), 2020)
Pilchak highlights the TMS 2020 Annual Meeting & Exhibition at "Purveyors of Processing Science and ICME: A Symposium to Honor the Many Contributions of Taylan Altan, Wei Tsu Wu, Soo-Ik Oh, and Lee Semiatin." Paying homage to the honorees' lifelong commitment to developing and validating process models, the symposium remained alloy-agnostic and instead kept central themes of processing, process simulation, and modeling the evolution of microstructure/texture/defects during processing. The symposium consisted of 37 technical talks organized into six technical sessions (Superalloys, Additive Manufacturing, Titanium alloys, Modeling and Simulation, Enhanced Properties via Thermomechanical Processing, and finally, Advances and Challenges in ICME). There were a large number of (28) invited talks where each speaker received 30-min allowing them to do thorough treatment of their subjects. Overall, the approach to inviting many speakers contributed to the high quality of the symposium and was well-received by the audience. There was excellent participation from industry, academia, and government laboratories.